Postoperative 30-day complications after cemented/hybrid versus cementless total hip arthroplasty in osteoarthritis patients > 70 years: A multicenter study from the Lundbeck Foundation Centre for Fast-track Hip and Knee replacement database and the Danish Hip Arthroplasty Register - Lindberg-Larsen, Martin (Acta Orthop, 2020)
Background and purpose — The use of cementless total hip arthroplasty (THA) in elderly patients is debated because of increased risk of early periprosthetic femoral fractures. However, cemented femoral components carry a risk of bone cement implantation syndrome. Hence, we compared in-hospital complications, complications leading to readmission and mortality ≤ 30 days postoperatively between hybrid/cemented (cemented femoral component) vs. cementless THA in osteoarthritis patients > 70 years. Patients and methods — This is a prospective observational cohort study in 9 centers from January 2010 to August 2017. We used 30-day follow-up from the Danish National Patient Registry, patient records, and data from the Danish Hip Arthroplasty Register. Only THAs performed as a result of osteoarthritis were included. Results — 3,368 (42%) of the THAs were cemented/hybrid and 4,728 (58%) cementless. The in-hospital complication risk was 7.7% after cemented/hybrid vs. 5.3% after cementless THA (< 0.001), statistically not significant when adjusting for comorbidities (p = 0.1). There were similar risks of complications causing readmission (5.7% vs. 6.2%) and mortality ≤ 30 days (0.2% vs. 0.3%). 15 cases (0.4%) of pulmonary embolism (PE) were found after cemented/hybrid vs. 4 (0.1%) after cementless THA (p = 0.001); none occurred within 24 hours postoperatively. 2 of the PEs after cementless THA led to mortality. Cemented/hybrid THA remained significantly associated with risk of PE (RR 3.9, p = 0.02), when adjusting for comorbidities. BMI > 35 was associated with highest risk of PE (RR 5.7, p = 0.003). The risk of periprosthetic femoral fracture was 0.2% after cemented/hybrid vs. 1.5% after cementless THA (p < 0.001) and the risk of dislocations was 1.2% after cemented/hybrid THA vs. 1.8% after cementless THA (p = 0.04). Interpretation — The higher risk of PE after cemented/hybrid THA and higher risk of periprosthetic femoral fractures and dislocations after cementless THA highlights that both medically and surgically complications are related to fixation technique and have to be considered.